Control thyself: Self-control failure and household wealth - Nina Biljanovska; Spyros Palligkinis (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
We examine the relationship between household wealth and self-control. Although self-control has been linked to consumption and financial behavior, its measurement remains an open issue. We employ a definition of self-control failure that follows literature in psychology, suggesting that three factors can render self-control defective: lack of planning, lack of monitoring, and lack of commitment to pre-set plans. Our measure combines those three ingredients and can be computed using a standard representative survey. We find that self-control failure is strongly associated with different household net wealth measures and with self-assessed financial distress.
Keywords: D01; D12; D14; 330; Self-Control; Household Wealth; Household Finance